Meningkatkan Pendidikan Biologi dengan Augmented dan Virtual Reality di Indonesia: Tinjauan Pustaka Sistematis - Najih, Riyan Riyadlun; Anasti, Chory Adenia; Putri, Marisha Nurlia Silvana; Ismi, Nur Qothima; Fatimah, Siti Khoirul; Azzahra, Zulfa; Sugiati, Nurlita Ayu; Nisa, Hairun; Ramadani, Risty Wulan Nita; Putri, Anida Aliva (UNHI Press, 2025)
Augmented Reality and Virtual Reality are increasingly used in biology and life sciences education. In the past decade, 34 Scopus-indexed studies (2015–2025) have examined their effects on conceptual understanding and scientific literacy. This study demonstrates that AR/VR meaningfully enhances biology learning by making lessons more immersive and interactive, thereby improving students' understanding of complex biological concepts and supporting higher-order thinking. AR helps visualize biological structures and processes, while VR enables exploration of human anatomy and virtual ecosystems. Despite these benefits, further long-term and comprehensive research is needed to better integrate AR/VR with other teaching methods. The study provides an overview of AR/VR use in Indonesian biology education, highlighting key research gaps, including the need for more evidence on long-term effects and practical classroom challenges. Together, these findings offer guidance for designing future technology-based biology instruction.